A high-elasticity thermal transfer film substrate and a preparation process thereof

CN122914698APending Publication Date: 2026-10-16SHANGHAI OUERTA SPECIAL PRINTING TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611203741.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]但是,传统热转印膜基材多采用PET、BOPP等非弹性塑料薄膜,存在明显缺陷:一是弹性不足,拉伸率通常低于100%,在弹性承印物表面转印后易出现图案开裂、脱落现象;二是定形性差,高温转印过程中易发生热变形,导致图案错位;三是阻隔性不足,油墨易渗透至基材内部,影响转印清晰度;四是离型层附着力不稳定,易出现离型不完全或转印时离型层随图案一起转移的问题;五是环保性差,多采用不可降解材料,废弃后易造成环境污染

Benefits of technology

[0017] Compared with existing technologies, the beneficial effects of this invention are: This invention achieves a synergistic unity of high elasticity, high shape retention, high barrier properties, and good release performance. The elastic reinforcing layer, prepared by supercritical carbon dioxide foaming of a blend of polylactic acid and poly(3-hydroxybutyrate-3-hydroxyvalerate), has a tensile elongation at break of over 300% and an elastic recovery rate of ≥90%, while also possessing complete biodegradability. The interpenetrating network structure barrier and shape-retaining layer, formed by crosslinking nanocellulose whiskers and polyvinyl alcohol with boric acid, has an oxygen permeability ≤8 cm⁻¹. 3 /(m 2 • 24h • 0.1MPa), high-temperature heat deformation rate ≤0.5%, effectively preventing ink penetration and ensuring transfer accuracy; glycidyl methacrylate grafted modified polylactic acid surface substrate layer, ink adhesion reaches level 0, significantly improving pattern transfer quality; composite release functional layer of anchoring bonding layer and release transfer layer, release force is stable at 0.5-1.2N/25mm, transfer qualification rate ≥98%; the overall preparation process adopts continuous production method, with high production efficiency, stable product performance, and all raw materials are environmentally friendly materials, meeting green manufacturing requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122914698A_ABST
    Figure CN122914698A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of hot transfer film preparation, in particular to a high-elasticity hot transfer film substrate and a preparation process thereof, which comprises a substrate bottom layer, wherein the substrate bottom layer is sequentially provided with an elasticity enhancement layer, a barrier setting layer and a surface printing layer from bottom to top. The application realizes the cooperation and unification of high elasticity, high setting property, high barrier property and good release performance, the elasticity enhancement layer prepared by supercritical carbon dioxide foaming of polylactic acid and poly-3-hydroxybutyrate-3-hydroxyvalerate blend has higher tensile elongation at break, the elasticity recovery rate is greater than or equal to 90%, and the elasticity enhancement layer has complete biodegradability; the interpenetrating network structure barrier setting layer formed by cross-linking of nanocellulose whiskers and polyvinyl alcohol through boric acid has a high-temperature thermal deformation rate less than or equal to 0.5%, effectively prevents ink penetration and ensures transfer precision.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of heat transfer film preparation technology, specifically to a highly elastic heat transfer film substrate and its preparation process. Background Technology

[0002] Heat transfer film is a functional film that transfers patterns onto the surface of a substrate through heat pressing. It is widely used in textiles, plastic products, leather products, packaging materials, and other fields. With the rapid development of industries such as flexible electronics, sportswear, and elastic packaging, higher requirements are being placed on the elasticity, shape retention, barrier properties, and environmental friendliness of heat transfer film substrates.

[0003] However, traditional heat transfer film substrates mostly use non-elastic plastic films such as PET and BOPP, which have obvious defects: First, they lack elasticity, with an elongation rate usually below 100%, making it easy for the pattern to crack and peel off after being transferred to an elastic substrate; second, they have poor shape retention, easily undergoing thermal deformation during high-temperature transfer, leading to pattern misalignment; third, they lack barrier properties, allowing ink to easily penetrate into the substrate, affecting the clarity of the transfer; fourth, the release layer adhesion is unstable, easily resulting in incomplete release or the release layer transferring along with the pattern during transfer; and fifth, they have poor environmental performance, often using non-degradable materials, which easily cause environmental pollution after disposal.

[0004] In summary, it is necessary to propose a highly elastic thermal transfer film substrate and its preparation process to solve the above problems. Summary of the Invention

[0005] The purpose of this invention is to provide a highly elastic thermal transfer film substrate and its preparation process to solve the problems mentioned in the background art.

[0006] To achieve the above objectives, the present invention provides the following technical solution: This invention proposes a highly elastic thermal transfer film substrate, comprising: The substrate bottom layer is provided with an elastic reinforcing layer, a barrier shaping layer and a surface printing layer from bottom to top; The elastic reinforcing layer is a closed-cell foam film made of a blend of polylactic acid and poly(3-hydroxybutyrate-3-hydroxyvalerate) through supercritical carbon dioxide foaming, with a thickness of 80-150 μm and a mass ratio of polylactic acid to poly(3-hydroxybutyrate-3-hydroxyvalerate) of 50:50-75:25. The barrier stabilizing layer is an interpenetrating network structure film formed by cross-linking nanocellulose whiskers and polyvinyl alcohol with boric acid. The diameter of the nanocellulose whiskers is 8-20 nm, the mass ratio of nanocellulose whiskers to polyvinyl alcohol is 1:2.5-1:5.5, and the amount of boric acid is 1.8%-3.5% of the mass of polyvinyl alcohol. The surface substrate is a polylactic acid film grafted with glycidyl methacrylate, with a grafting rate of 1.0%-2.0%, and the surface is treated with corona to achieve a dyne value of 48-56. A release functional layer is coated on top of the surface printing layer, and the release functional layer is provided with an anchoring bonding layer and a release transfer layer from bottom to top; The anchoring bonding layer is a hybrid coating composed of acrylate-vinyl acetate copolymer emulsion, nano-silica sol and waterborne polyurethane crosslinking agent. The mass ratio of acrylate-vinyl acetate copolymer emulsion, nano-silica sol and waterborne polyurethane crosslinking agent is 15-25:2-4:1-3. The silica particles in the nano-silica sol have a particle size of 10-25 nm. The release transfer layer is a hot-melt release coating composed of polyethylene wax emulsion, polydimethylsiloxane and nano talc powder. The mass ratio of polyethylene wax emulsion, polydimethylsiloxane and nano talc powder is 10-20:3-7:1-3, and the thickness of the nano talc powder sheet is 30-60 nm. The substrate bottom layer also includes an elastic buffer bottom layer disposed on the lower surface of the elastic reinforcement layer. The elastic buffer bottom layer is a composite film obtained by solution blending and casting of thermoplastic polyurethane and nano hydroxyapatite, with a thickness of 55 μm. The thermoplastic polyurethane has a Shore hardness of 80A, the nano hydroxyapatite has a particle size of 60 nm, and the amount of nano hydroxyapatite is 5% of the mass of thermoplastic polyurethane.

[0007] Preferably, in the elastic reinforcing layer, the L-lactic acid content of polylactic acid is 94%-98%, and the number average molecular weight is 8×10⁻⁶. 4 -15×10 4 g / mol; the molar content of 3-hydroxyvalerate in poly-3-hydroxybutyrate-3-hydroxyvalerate is 12%-20%, and the number average molecular weight is 3×10⁻⁶ g / mol. 5 -6×10 5 g / mol.

[0008] Preferably, the elastic reinforcing layer is prepared by supercritical carbon dioxide autoclaving process, with a saturation pressure of 14-20 MPa, a saturation temperature of 70-95℃, a saturation time of 2-4 hours, and a depressurization rate of 10-18 MPa / s, resulting in a closed-cell foam film with an average cell diameter of 20-50 μm.

[0009] Preferably, in the barrier shaping layer, the degree of alcoholysis of polyvinyl alcohol is 88%-99%, the degree of polymerization is 1700-2400, and the nanocellulose whiskers are rod-shaped whiskers obtained by sulfuric acid hydrolysis of cotton pulp, with an aspect ratio of 15-30.

[0010] Preferably, in the surface printing layer, the L-lactic acid content of polylactic acid is 96%-99%, and the number average molecular weight is 1×10⁻⁶. 5 -2×10 5 The grafting reaction was initiated with dicumyl peroxide as the initiator, and the amount of dicumyl peroxide was 0.15%-0.5% of the mass of polylactic acid.

[0011] Preferably, the grafting reaction of the glycidyl methacrylate-grafted polylactic acid is carried out by reactive extrusion process, with the temperature of each zone of the twin-screw extruder being 140-155℃ in the feeding section, 165-180℃ in the plasticizing section, 180-195℃ in the metering section, and 170-185℃ in the die head, and the screw speed being 60-100 rpm.

[0012] Preferably, the elastic buffer underlayer is prepared by dissolving thermoplastic polyurethane particles in N,N-dimethylformamide to prepare a 14% (w / w) solution, adding 60nm nano-hydroxyapatite (5% of the mass of the thermoplastic polyurethane), dispersing at 2500rpm for 25min to obtain a uniform dispersion, degassing under vacuum, casting on a glass substrate, gradient drying at 60℃ for 3.5 hours, followed by annealing at 105℃ for 35min to obtain an elastic buffer underlayer film; then, the elastic buffer underlayer is hot-pressed onto the lower surface of the elastic reinforcing layer at 110℃ and 0.3MPa to obtain an elastic reinforcing layer with an elastic buffer underlayer.

[0013] Preferably, in the anchoring bonding layer, the acrylate structural unit of the acrylate-vinyl acetate copolymer emulsion is a copolymer of butyl acrylate and methyl methacrylate, the mass ratio of butyl acrylate to methyl methacrylate is 50:50-60:40, the vinyl acetate content is 15%-25% of the solid content of the copolymer emulsion, and the waterborne polyurethane crosslinking agent is a blocked isocyanate crosslinking agent with a deblocking temperature of 110-130℃.

[0014] Preferably, in the release transfer layer, the polyethylene wax emulsion has a polyethylene wax melting point of 105-120℃ and an average particle size of 2-6μm, the polydimethylsiloxane has a viscosity of 350-1000cSt, and the nano-talc powder has an aspect ratio of 10-25.

[0015] Based on the highly elastic thermal transfer film substrate, this invention also proposes a preparation process for the highly elastic thermal transfer film substrate, comprising the following steps: S1. Preparation of elastic reinforcing layer: Polylactic acid granules and poly(3-hydroxybutyrate-3-hydroxyvalerate) granules are premixed at a mass ratio of 50:50-75:25 and fed into a twin-screw extruder for melt blending and granulation. The extrusion temperature zones are set as follows: feeding section 155-170℃, plasticizing section 170-185℃, metering section 180-195℃, and die head 175-190℃. The screw speed is 120-180 rpm. The resulting blended granules are fed into a high-pressure autoclave and supercritical carbon dioxide is introduced for saturation permeation. The saturation pressure is 14-20 MPa, the saturation temperature is 70-95℃, and the saturation time is 2-4 hours. Then, the pressure is released and foamed at a rate of 10-18 MPa / s to obtain a closed-cell foam film. S2. Preparation of the barrier and shaping layer: Aqueous dispersion of nanocellulose whiskers and aqueous solution of polyvinyl alcohol are mixed at a mass ratio of nanocellulose whiskers to polyvinyl alcohol of 1:2.5-1:5.5. Aqueous solution of boric acid is added, with the amount of boric acid being 1.8%-3.5% of the mass of polyvinyl alcohol. The mixture is stirred and reacted at 75-85℃ for 30-50 min to form a precursor sol. The precursor sol is cast onto the upper surface of the elastic reinforcing layer obtained in S1 and dried in a constant temperature drying oven at 35-45℃ for 5-7 hours to form a semi-interpenetrating network gel film. Subsequently, the film is heat-treated in a hot air drying tunnel at 125-135℃ for 15-25 min to complete the crosslinking of boric acid and form an interpenetrating network structure film, thus obtaining an integrated composite film of elastic reinforcing layer and barrier and shaping layer. S3. Preparation of surface printing layer: Polylactic acid granules, glycidyl methacrylate monomer and dicumyl peroxide initiator are premixed. The amount of dicumyl peroxide is 0.15%-0.5% of the mass of polylactic acid. The mixture is fed into a twin-screw extruder for reactive extrusion grafting. The temperatures of each zone of the extruder are 140-155℃ in the feeding section, 165-180℃ in the plasticizing section, 180-195℃ in the metering section and 170-185℃ in the die head. The screw speed is 60-100 rpm. The resulting grafted modified granules are fed into a single-screw casting machine for casting into a film. The casting temperature is 190-210℃. After the cast film is cooled to room temperature, it is subjected to corona treatment to a dyne value of 48-56 to obtain the surface printing layer film. S4. The surface printing layer film obtained in S3 is hot-pressed onto the barrier shaping layer of the integrated composite film obtained in S2. The hot-pressing temperature is 135-150℃, the pressure is 0.3-0.5MPa, and the linear speed is 2-3m / min to obtain the substrate bottom layer. S5. Preparation of the release functional layer: On the surface printing layer of the substrate obtained in S4, an anchoring bonding layer mixture is first rolled onto it. The anchoring bonding layer mixture is composed of acrylate-vinyl acetate copolymer emulsion, nano silica sol and waterborne polyurethane crosslinking agent in a mass ratio of 15-25:2-4:1-3, with a wet film thickness of 30-50 μm. It is dried in an oven at 70-80℃ for 6-10 min. Then, a release transfer layer mixture is rolled onto the anchoring bonding layer. The release transfer layer mixture is composed of polyethylene wax emulsion, polydimethylsiloxane and nano talc powder in a mass ratio of 10-20:3-7:1-3, with a wet film thickness of 20-30 μm. It is dried in an oven at 80-90℃ for 4-6 min to obtain a high-elasticity heat transfer film substrate.

[0016] Preferably, the anchoring bonding layer mixture in step S5 is ultrasonically dispersed at 300-500W for 10-20 minutes before roller coating, and the release transfer layer mixture is high-speed dispersed at 2500-3500rpm for 15-25 minutes before roller coating; after drying in step S5, the rolled film is left to stand in a curing chamber at 40-50℃ for 60-84 hours.

[0017] Compared with existing technologies, the beneficial effects of this invention are: This invention achieves a synergistic unity of high elasticity, high shape retention, high barrier properties, and good release performance. The elastic reinforcing layer, prepared by supercritical carbon dioxide foaming of a blend of polylactic acid and poly(3-hydroxybutyrate-3-hydroxyvalerate), has a tensile elongation at break of over 300% and an elastic recovery rate of ≥90%, while also possessing complete biodegradability. The interpenetrating network structure barrier and shape-retaining layer, formed by crosslinking nanocellulose whiskers and polyvinyl alcohol with boric acid, has an oxygen permeability ≤8 cm⁻¹. 3 / (m 2 • 24h • 0.1MPa), high-temperature heat deformation rate ≤0.5%, effectively preventing ink penetration and ensuring transfer accuracy; glycidyl methacrylate grafted modified polylactic acid surface substrate layer, ink adhesion reaches level 0, significantly improving pattern transfer quality; composite release functional layer of anchoring bonding layer and release transfer layer, release force is stable at 0.5-1.2N / 25mm, transfer qualification rate ≥98%; the overall preparation process adopts continuous production method, with high production efficiency, stable product performance, and all raw materials are environmentally friendly materials, meeting green manufacturing requirements. Attached Figure Description

[0018] Figure 1 This is a flowchart of the preparation method of the high-elasticity thermal transfer film substrate of the present invention. Detailed Implementation

[0019] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0020] I. Materials: Unless otherwise specified, all components of the high-elasticity heat transfer film substrate formulation of this invention are commercially available. This invention proposes a highly elastic thermal transfer film substrate, comprising a substrate bottom layer and a release functional layer.

[0021] The substrate bottom layer is provided with an elastic reinforcement layer, a barrier shaping layer and a surface printing layer from bottom to top.

[0022] The elastic reinforcing layer is a closed-cell foam film made of a blend of polylactic acid (PLA) and poly(3-hydroxybutyrate-3-hydroxyvalerate) through supercritical carbon dioxide foaming, with a thickness of 80-150 μm and a mass ratio of PLA to PLA of 50:50-75:25. The PLA contains 94%-98% L-lactic acid and has a number-average molecular weight of 8 × 10⁻⁶. 4 -15×10 4 g / mol; the molar content of 3-hydroxyvalerate in poly-3-hydroxybutyrate-3-hydroxyvalerate is 12%-20%, and the number average molecular weight is 3×10⁻⁶ g / mol. 5 -6×10 5 g / mol. The elastic reinforcing layer is prepared by supercritical carbon dioxide autoclaving process, with a saturation pressure of 14-20 MPa, a saturation temperature of 70-95℃, a saturation time of 2-4 hours, and a depressurization rate of 10-18 MPa / s. The average cell diameter of the resulting closed-cell foam film is 20-50 μm.

[0023] The barrier and shaping layer is an interpenetrating network structure film formed by cross-linking nanocellulose whiskers and polyvinyl alcohol with boric acid. The nanocellulose whiskers have a diameter of 8-20 nm, the mass ratio of nanocellulose whiskers to polyvinyl alcohol is 1:2.5-1:5.5, and the amount of boric acid is 1.8%-3.5% of the mass of polyvinyl alcohol. The degree of alcoholysis of polyvinyl alcohol is 88%-99%, the degree of polymerization is 1700-2400, and the nanocellulose whiskers are rod-shaped whiskers obtained from sulfuric acid hydrolysis of cotton pulp, with an aspect ratio of 15-30.

[0024] The surface substrate is a polylactic acid film grafted with glycidyl methacrylate, with a grafting rate of 1.0%-2.0%, and the surface is corona-treated to a dyne value of 48-56. The polylactic acid contains 96%-99% L-lactic acid and has a number-average molecular weight of 1×10⁻⁶.5 -2×10 5 The grafting reaction was carried out using dicumyl peroxide as an initiator, with the amount of dicumyl peroxide being 0.15%-0.5% of the mass of polylactic acid. The grafting reaction of the glycidyl methacrylate-modified polylactic acid was performed using a reactive extrusion process. The temperatures of each zone of the twin-screw extruder were as follows: feeding section 140-155℃, plasticizing section 165-180℃, metering section 180-195℃, and die head 170-185℃; the screw speed was 60-100 rpm. The elastic buffer underlayer is prepared by dissolving thermoplastic polyurethane particles in N,N-dimethylformamide to prepare a 14% (w / w) solution, adding 60nm nano-hydroxyapatite (5% of the mass of the thermoplastic polyurethane), and dispersing at 2500rpm for 25min to obtain a uniform dispersion. After vacuum degassing, the dispersion is cast onto a glass substrate and dried at 60℃ for 3.5 hours. Then, it is annealed at 105℃ for 35min to obtain an elastic buffer underlayer film. The elastic buffer underlayer is then hot-pressed onto the lower surface of the elastic reinforcement layer at 110℃ and 0.3MPa to obtain an elastic reinforcement layer with an elastic buffer underlayer.

[0025] The release functional layer is coated on top of the surface printing layer, and the release functional layer is provided with an anchoring bonding layer and a release transfer layer from bottom to top.

[0026] The anchoring bonding layer is a hybrid coating composed of an acrylate-vinyl acetate copolymer emulsion, nano-silica sol, and a waterborne polyurethane crosslinking agent. The mass ratio of the acrylate-vinyl acetate copolymer emulsion, nano-silica sol, and waterborne polyurethane crosslinking agent is 15-25:2-4:1-3, and the silica particles in the nano-silica sol have a particle size of 10-25 nm. The acrylate structural unit of the acrylate-vinyl acetate copolymer emulsion is a copolymer of butyl acrylate and methyl methacrylate, with a mass ratio of butyl acrylate to methyl methacrylate of 50:50-60:40. The vinyl acetate content is 15%-25% of the solid content of the copolymer emulsion. The waterborne polyurethane crosslinking agent is a blocked isocyanate crosslinking agent with a deblocking temperature of 110-130℃.

[0027] The release transfer layer is a hot-melt release coating composed of polyethylene wax emulsion, polydimethylsiloxane, and nano-talc powder. The mass ratio of the polyethylene wax emulsion, polydimethylsiloxane, and nano-talc powder is 10-20:3-7:1-3, and the thickness of the nano-talc powder sheet is 30-60 nm. Specifically, the polyethylene wax emulsion has a melting point of 105-120℃ and an average particle size of 2-6 μm; the polydimethylsiloxane has a viscosity of 350-1000 cSt; and the nano-talc powder has an aspect ratio of 10-25. The substrate bottom layer also includes an elastic buffer bottom layer disposed on the lower surface of the elastic reinforcement layer. The elastic buffer bottom layer is a composite film obtained by solution blending and casting of thermoplastic polyurethane and nano hydroxyapatite, with a thickness of 55 μm. The thermoplastic polyurethane has a Shore hardness of 80A, the nano hydroxyapatite has a particle size of 60 nm, and the amount of nano hydroxyapatite is 5% of the mass of thermoplastic polyurethane.

[0028] II. Process: Please see Figure 1 Based on the above formulation, this invention also proposes a method for preparing a highly elastic thermal transfer film substrate, specifically including the following steps: S1. Preparation of elastic reinforcing layer: Polylactic acid granules and poly(3-hydroxybutyrate-3-hydroxyvalerate) granules are premixed at a mass ratio of 50:50-75:25 and fed into a twin-screw extruder for melt blending and granulation. The extrusion temperature zones are set as follows: feeding section 155-170℃, plasticizing section 170-185℃, metering section 180-195℃, and die head 175-190℃. The screw speed is 120-180 rpm. The resulting blended granules are fed into a high-pressure autoclave and supercritical carbon dioxide is introduced for saturation permeation. The saturation pressure is 14-20 MPa, the saturation temperature is 70-95℃, and the saturation time is 2-4 hours. Then, the pressure is released and foamed at a rate of 10-18 MPa / s to obtain a closed-cell foam film. S2. Preparation of the barrier and shaping layer: Aqueous dispersion of nanocellulose whiskers and aqueous solution of polyvinyl alcohol are mixed at a mass ratio of nanocellulose whiskers to polyvinyl alcohol of 1:2.5-1:5.5. Aqueous solution of boric acid is added, with the amount of boric acid being 1.8%-3.5% of the mass of polyvinyl alcohol. The mixture is stirred and reacted at 75-85℃ for 30-50 min to form a precursor sol. The precursor sol is cast onto the upper surface of the elastic reinforcing layer obtained in S1 and dried in a constant temperature drying oven at 35-45℃ for 5-7 hours to form a semi-interpenetrating network gel film. Subsequently, the film is heat-treated in a hot air drying tunnel at 125-135℃ for 15-25 min to complete the crosslinking of boric acid and form an interpenetrating network structure film, thus obtaining an integrated composite film of elastic reinforcing layer and barrier and shaping layer. S3. Preparation of surface printing layer: Polylactic acid granules, glycidyl methacrylate monomer and dicumyl peroxide initiator are premixed. The amount of dicumyl peroxide is 0.15%-0.5% of the mass of polylactic acid. The mixture is fed into a twin-screw extruder for reactive extrusion grafting. The temperatures of each zone of the extruder are 140-155℃ in the feeding section, 165-180℃ in the plasticizing section, 180-195℃ in the metering section and 170-185℃ in the die head. The screw speed is 60-100 rpm. The resulting grafted modified granules are fed into a single-screw casting machine for casting into a film. The casting temperature is 190-210℃. After the cast film is cooled to room temperature, it is subjected to corona treatment to a dyne value of 48-56 to obtain the surface printing layer film. S4. The surface printing layer film obtained in S3 is hot-pressed onto the barrier shaping layer of the integrated composite film obtained in S2. The hot-pressing temperature is 135-150℃, the pressure is 0.3-0.5MPa, and the linear speed is 2-3m / min to obtain the substrate bottom layer. S5. Preparation of the release functional layer: On the surface of the substrate obtained in S4, the anchoring bonding layer mixture is first rolled onto the bottom layer. The anchoring bonding layer mixture is made by mixing acrylate-vinyl acetate copolymer emulsion, nano silica sol and waterborne polyurethane crosslinking agent in a mass ratio of 15-25:2-4:1-3, with a wet film thickness of 30-50 μm. It is then dried in an oven at 70-80℃ for 6-10 min. Subsequently, the release transfer layer mixture is rolled onto the anchoring bonding layer. The release transfer layer mixture is made by mixing polyethylene wax emulsion, polydimethylsiloxane and nano talc in a mass ratio of 10-20:3-7:1-3, with a wet film thickness of 20-30 μm. It is then dried in an oven at 80-90℃ for 4-6 min. After drying, the rolled-up film is left to stand in a curing chamber at 40-50℃ for 60-84 hours to obtain a high-elasticity heat transfer film substrate.

[0029] It should be noted that the anchoring bonding layer mixture in step S5 is ultrasonically dispersed at 300-500W for 10-20 minutes before roller coating, and the release transfer layer mixture is high-speed dispersed at 2500-3500rpm for 15-25 minutes before roller coating.

[0030] Example 1: In this example, a highly elastic thermal transfer film substrate was prepared according to the following process, with the following formulation components: Elastic reinforcement layer: Polylactic acid (L-lactic acid content 96%, number average molecular weight 12×10⁻⁶) 4 60 parts (g / mol) of poly(3-hydroxybutyrate-3-hydroxyvalerate) (3-hydroxyvalerate molar content 16%, number average molecular weight 4.5×10⁻⁶ g / mol), 5 40 portions (g / mol) with a thickness of 110 μm; Barrier and shaping layer: 1 part of nanocellulose whiskers (diameter 14nm, aspect ratio 22), 4 parts of polyvinyl alcohol (degree of alcoholysis 94%, degree of polymerization 2000), and 0.1 parts of boric acid (2.5% of the mass of polyvinyl alcohol). Surface substrate: Polylactic acid (L-lactic acid content 98%, number average molecular weight 1.5×10⁻⁶) 5 100 parts (g / mol), 1.5 parts glycidyl methacrylate, 0.3 parts dicumyl peroxide, grafting rate 1.5%, corona treatment dyne value 52; Anchoring bonding layer: 20 parts of acrylate-vinyl acetate copolymer emulsion (butyl acrylate: methyl methacrylate = 55:45, vinyl acetate content 20%), 3 parts of nano silica sol (particle size 18nm), and 2 parts of waterborne polyurethane crosslinking agent (unsealing temperature 120℃). Release transfer layer: 15 parts of polyethylene wax emulsion (melting point 112℃, average particle size 4μm), 5 parts of polydimethylsiloxane (viscosity 650cSt), and 2 parts of nano talc powder (sheet thickness 45nm, aspect ratio 18). Includes the following steps: Step 1: Prepare the elastic reinforcement layer: 60 parts of polylactic acid granules and 40 parts of poly(3-hydroxybutyrate-3-hydroxyvalerate) granules were premixed and fed into a twin-screw extruder for melt blending and granulation. The extrusion temperature zones were set as follows: feeding section 162℃, plasticizing section 178℃, metering section 188℃, and die head 182℃. The screw speed was 150 rpm. The resulting blended granules were fed into a high-pressure reactor and saturated with supercritical carbon dioxide for saturation permeation. The saturation pressure was 17 MPa, the saturation temperature was 82℃, and the saturation time was 3 hours. Subsequently, the pressure was released and foamed at a rate of 14 MPa / s to obtain a closed-cell foam film with an average cell diameter of 35 μm and a thickness of 110 μm. Step 2: Prepare the barrier shaping layer: Aqueous dispersion of nanocellulose whiskers (1% solid content) and aqueous solution of polyvinyl alcohol (10% solid content) were mixed at a mass ratio of 1:4. Aqueous solution of boric acid (5% solid content) was added, with the amount of boric acid being 2.5% of the mass of polyvinyl alcohol. The mixture was stirred at 80°C for 40 min to form a precursor sol. The precursor sol was cast onto the upper surface of the elastic reinforcing layer obtained in step 1 and dried in a constant temperature drying oven at 40°C for 6 hours to form a semi-interpenetrating network gel film. Subsequently, the film was heat-treated in a hot air drying tunnel at 130°C for 20 min to complete the crosslinking of boric acid and form an interpenetrating network structure film, thus obtaining an integrated composite film of elastic reinforcing layer and barrier shaping layer. Step 3: Prepare the surface substrate layer: 100 parts of polylactic acid granules, 1.5 parts of glycidyl methacrylate monomer, and 0.3 parts of dicumyl peroxide initiator were premixed and fed into a twin-screw extruder for reactive extrusion grafting. The temperatures of each zone of the extruder were 148°C in the feeding section, 172°C in the plasticizing section, 188°C in the metering section, and 178°C in the die head. The screw speed was 80 rpm. The resulting grafted modified granules were fed into a single-screw casting machine to cast a film at a casting temperature of 200°C. After the cast film was cooled to room temperature, it was corona treated to a dyne value of 52 to obtain a surface printing layer film. Step 4: Hot pressing composite preparation of the substrate bottom layer: The surface printing layer film obtained in step 3 is hot-pressed onto the barrier shaping layer of the integrated composite film obtained in step 2. The hot-pressing temperature is 142℃, the pressure is 0.4MPa, and the linear speed is 2.5m / min to obtain the substrate bottom layer. Step 5: Prepare the release functional layer: 20 parts of acrylate-vinyl acetate copolymer emulsion, 3 parts of nano silica sol and 2 parts of waterborne polyurethane crosslinking agent were mixed and ultrasonically dispersed at 400W for 15 minutes to obtain the anchoring bonding layer mixture; the anchoring bonding layer mixture was roller coated on the surface printing layer of the substrate bottom layer obtained in step 4, with a wet film thickness of 40μm, and dried in a 75℃ oven for 8 minutes. 15 parts of polyethylene wax emulsion, 5 parts of polydimethylsiloxane and 2 parts of nano talc powder were mixed and dispersed at high speed of 3000 rpm for 20 min to obtain a release transfer layer mixture; the release transfer layer mixture was roller coated on the anchoring bonding layer with a wet film thickness of 25 μm and dried in an oven at 85℃ for 5 min. After drying, the rolled-up film is left to stand in a curing chamber at 45°C for 72 hours to obtain a high-elasticity heat transfer film substrate.

[0031] Example 2, in this example, the formulation components are: Elastic reinforcement layer: Polylactic acid (L-lactic acid content 94%, number average molecular weight 8×10) 4 50 parts of poly(3-hydroxybutyrate-3-hydroxyvalerate) (3-hydroxyvalerate molar content 12%, number average molecular weight 3×10 g / mol), 5 50 portions (g / mol) with a thickness of 80 μm; Barrier and shaping layer: 1 part of nanocellulose whiskers (diameter 8nm, aspect ratio 15), 2.5 parts of polyvinyl alcohol (degree of alcoholysis 88%, degree of polymerization 1700), and 0.045 parts of boric acid (1.8% of the mass of polyvinyl alcohol). Surface substrate: Polylactic acid (L-lactic acid content 96%, number average molecular weight 1×10⁻⁶) 5 100 parts (g / mol), 1.0 part glycidyl methacrylate, 0.15 parts dicumyl peroxide, grafting rate 1.0%, corona treatment dyne value 48; Anchoring bonding layer: 15 parts of acrylate-vinyl acetate copolymer emulsion (butyl acrylate: methyl methacrylate = 50:50, vinyl acetate content 15%), 2 parts of nano silica sol (particle size 10nm), and 1 part of waterborne polyurethane crosslinking agent (unsealing temperature 110℃). Release transfer layer: 10 parts of polyethylene wax emulsion (melting point 105℃, average particle size 2μm), 3 parts of polydimethylsiloxane (viscosity 350cSt), and 1 part of nano talc powder (sheet thickness 30nm, aspect ratio 10). Other process parameters are the same as in Example 1.

[0032] Example 3, in this example, the formulation components are: Elastic reinforcement layer: Polylactic acid (L-lactic acid content 98%, number average molecular weight 15×10⁻⁶) 475 parts (g / mol), poly(3-hydroxybutyrate-3-hydroxyvalerate) (3-hydroxyvalerate molar content 20%, number average molecular weight 6×10⁻⁶ g / mol), 5 25 portions (g / mol) with a thickness of 150 μm; Barrier and shaping layer: 1 part of nanocellulose whiskers (diameter 20nm, aspect ratio 30), 5.5 parts of polyvinyl alcohol (degree of alcoholysis 99%, degree of polymerization 2400), and 0.1925 parts of boric acid (3.5% of the mass of polyvinyl alcohol). Surface substrate: Polylactic acid (L-lactic acid content 99%, number average molecular weight 2×10⁻⁶) 5 100 parts (g / mol), 2.0 parts glycidyl methacrylate, 0.5 parts dicumyl peroxide, grafting rate 2.0%, corona treatment dyne value 56; Anchoring bonding layer: 25 parts of acrylate-vinyl acetate copolymer emulsion (butyl acrylate: methyl methacrylate = 60:40, vinyl acetate content 25%), 4 parts of nano silica sol (particle size 25nm), and 3 parts of waterborne polyurethane crosslinking agent (unsealing temperature 130℃). Release transfer layer: 20 parts of polyethylene wax emulsion (melting point 120℃, average particle size 6μm), 7 parts of polydimethylsiloxane (viscosity 1000cSt), and 3 parts of nano talc powder (sheet thickness 60nm, aspect ratio 25). Other process parameters are the same as in Example 1.

[0033] The material parameters of the high-elasticity thermal transfer film substrate prepared in the examples are shown in Table 1: Table 1. Material parameters of the high-elasticity heat transfer film substrate prepared in the examples. Polylactic acid (elastic reinforcing layer, part number) 60 50 75 PHBV (elastic reinforcing layer, part number) 40 50 25 Elastic reinforcement layer thickness (μm) 110 80 150 Nanocellulose whiskers (parts) 1 1 1 Polyvinyl alcohol (parts) 4 2.5 5.5 Boric acid dosage (PVA mass%) 2.5 1.8 3.5 GMA grafting rate (%) 1.5 1.0 2.0 Surface dyne value 52 48 56 Acrylic ester-vinyl acetate emulsion (parts) 20 15 25 Nano silica sol (parts) 3 2 4 Waterborne polyurethane crosslinking agent (parts) 2 1 3 Polyethylene wax emulsion (parts) 15 10 20 Polydimethylsiloxane (parts) 5 3 7 Nano talc powder (parts) 2 1 3 Comparative Example 1: In this comparative example, the mass ratio of polylactic acid to PHBV in the elastic reinforcing layer is 80:20, and other formulation components and process parameters are the same as in Example 1.

[0034] Comparative Example 2: In this comparative example, the amount of boric acid in the barrier sizing layer was 1.0% of the mass of polyvinyl alcohol, and the other formulation components and process parameters were the same as in Example 1.

[0035] Comparative Example 3: In this comparative example, the amount of polydimethylsiloxane in the release transfer layer was 10 parts, and the other formulation components and process parameters were the same as in Example 1.

[0036] The material parameters of the high-elasticity thermal transfer film substrate prepared in the comparative example are shown in Table 2: Table 2. Material parameters of the high-elasticity heat transfer film substrates prepared in the comparative examples. Polylactic acid (elastic reinforcing layer, part number) 80 60 60 PHBV (elastic reinforcing layer, part number) 20 40 40 Elastic reinforcement layer thickness (μm) 110 110 110 Nanocellulose whiskers (parts) 1 1 1 Polyvinyl alcohol (parts) 4 4 4 Boric acid dosage (PVA mass%) 2.5 1.0 2.5 GMA grafting rate (%) 1.5 1.5 1.5 Surface dyne value 52 52 52 Acrylic ester-vinyl acetate emulsion (parts) 20 20 20 Nano silica sol (parts) 3 3 3 Waterborne polyurethane crosslinking agent (parts) 2 2 2 Polyethylene wax emulsion (parts) 15 15 15 Polydimethylsiloxane (parts) 5 5 10 Nano talc powder (parts) 2 2 2 III. Performance Testing: The following performance tests were performed on the highly elastic thermal transfer film substrates prepared in the examples and comparative examples: a. According to GB / T1040.3-2006 "Determination of tensile properties of plastics - Part 3: Films and sheets", the tensile elongation at break and elastic recovery rate were tested (stretched to 200% elongation and held for 1 min, and the residual deformation was measured 30 min after unloading, and the elastic recovery rate was calculated). b. Test the oxygen transmission rate (23℃, 0%RH) according to GB / T1038-2000 "Gas Permeability Test Method for Plastic Films and Sheets - Differential Pressure Method"; c. Test the ink adhesion according to GB / T9286-1998 "Cross-cut test of paint and varnish film" (after printing with heat transfer ink, hot press at 150℃ for 10s, and then perform cross-cut test after cooling). d. Test the 180° release force (peeling speed 300 mm / min) according to GB / T25256-2010 "Test Method for 180° Peel Force and Residual Adhesion of Optical Functional Film Release Film". e. Heat set test: Heat the membrane material in an oven at 150℃ for 30 seconds, remove it and cool it to room temperature, and measure the rate of dimensional change. f. Transfer rate test: After printing the pattern on the film material, it is hot-pressed at 150℃ and 0.3MPa pressure for 10s to transfer it to the surface of spandex fabric. 100 transfer samples are observed, and the number of qualified samples without cracks, missing prints, or misalignments is counted. The transfer rate is then calculated.

[0037] Performance data for the examples and comparative examples are shown in Table 3: Table 3 Performance data for examples and comparative examples Elongation at break (%) 350 380 320 200 340 345 Elastic recovery rate (%) 92 94 90 75 91 91 Oxygen permeability (cm3 / (m2・24h・0.1MPa)) 5 7 6 6 28 5 Ink adhesion (grade) 0 0 0 0 0 0 180° release force (N / 25mm) 0.8 0.6 1.1 0.8 0.8 2.6 Dimensional change rate of heat set (%) 0.3 0.4 0.3 0.3 1.6 0.3 Transfer printing pass rate (%) 99 98 98 82 85 78 IV. Analysis Conclusion: As shown in Tables 2 and 3, in Comparative Example 1, the excessive polylactic acid ratio led to a decrease in the flexibility of the elastic reinforcing layer, a 43% reduction in tensile elongation at break, and an 18% reduction in elastic recovery rate. The transferred pattern was prone to cracking due to stretching, resulting in a transfer pass rate of only 82%. In Comparative Example 2, insufficient boric acid resulted in incomplete cross-linking of polyvinyl alcohol and nanocellulose whiskers, a less dense network structure in the barrier layer, a 460% increase in oxygen permeability, and a 433% increase in high-temperature heat distortion rate. This made ink penetration and pattern misalignment more likely during the transfer process, reducing the transfer pass rate to 85%. In Comparative Example 3, excessive polydimethylsiloxane resulted in excessive release force in the release transfer layer, preventing complete pattern transfer and resulting in a transfer pass rate of only 78%. These findings verify the scientific validity of the component range of the high-elasticity thermal transfer film substrate in this invention.

[0038] According to Tables 1 and 3, the proportions of each component in Example 1 of this invention are balanced. 60 parts of polylactic acid and 40 parts of PHBV synergistically provide excellent elasticity and toughness, with a tensile elongation at break of 350% and an elastic recovery rate of 92%. One part of nanocellulose whiskers and four parts of polyvinyl alcohol form a dense interpenetrating network structure with 2.5% boric acid, resulting in an oxygen permeability as low as 5 cm⁻¹. 3 / (m 2 • 24h • 0.1MPa), the dimensional change rate of heat setting is only 0.3%; the ink adhesion of the GMA grafted modified polylactic acid surface substrate reaches level 0, and the composite structure of the anchoring bonding layer and the release transfer layer provides a stable release force of 0.8N / 25mm, with a transfer qualification rate of up to 99%, and the best overall performance.

[0039] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A highly elastic thermal transfer film substrate, characterized in that, include: The substrate bottom layer is provided with an elastic reinforcing layer, a barrier shaping layer and a surface printing layer from bottom to top; The elastic reinforcing layer is a closed-cell foam film made of a blend of polylactic acid and poly(3-hydroxybutyrate-3-hydroxyvalerate) through supercritical carbon dioxide foaming, with a thickness of 80-150 μm and a mass ratio of polylactic acid to poly(3-hydroxybutyrate-3-hydroxyvalerate) of 50:50-75:

25. The barrier stabilizing layer is an interpenetrating network structure film formed by cross-linking nanocellulose whiskers and polyvinyl alcohol with boric acid. The diameter of the nanocellulose whiskers is 8-20 nm, the mass ratio of nanocellulose whiskers to polyvinyl alcohol is 1:2.5-1:5.5, and the amount of boric acid is 1.8%-3.5% of the mass of polyvinyl alcohol. The surface substrate is a polylactic acid film grafted with glycidyl methacrylate, with a grafting rate of 1.0%-2.0%, and the surface is treated with corona to achieve a dyne value of 48-56. A release functional layer is coated on top of the surface printing layer, and the release functional layer is provided with an anchoring bonding layer and a release transfer layer from bottom to top; The anchoring bonding layer is a hybrid coating composed of acrylate-vinyl acetate copolymer emulsion, nano-silica sol and waterborne polyurethane crosslinking agent. The mass ratio of acrylate-vinyl acetate copolymer emulsion, nano-silica sol and waterborne polyurethane crosslinking agent is 15-25:2-4:1-3. The silica particles in the nano-silica sol have a particle size of 10-25 nm. The release transfer layer is a hot-melt release coating composed of polyethylene wax emulsion, polydimethylsiloxane and nano talc powder. The mass ratio of polyethylene wax emulsion, polydimethylsiloxane and nano talc powder is 10-20:3-7:1-3, and the thickness of the nano talc powder sheet is 30-60 nm. The substrate bottom layer also includes an elastic buffer bottom layer disposed on the lower surface of the elastic reinforcement layer. The elastic buffer bottom layer is a composite film obtained by solution blending and casting of thermoplastic polyurethane and nano hydroxyapatite, with a thickness of 55 μm. The thermoplastic polyurethane has a Shore hardness of 80A, the nano hydroxyapatite has a particle size of 60 nm, and the amount of nano hydroxyapatite is 5% of the mass of thermoplastic polyurethane.

2. The highly elastic thermal transfer film substrate according to claim 1, characterized in that, In the elastic reinforcing layer, the L-lactic acid content of polylactic acid is 94%-98%, and the number average molecular weight is 8×10⁻⁶. 4 -15×10 4 g / mol; the molar content of 3-hydroxyvalerate in poly-3-hydroxybutyrate-3-hydroxyvalerate is 12%-20%, and the number average molecular weight is 3×10⁻⁶ g / mol. 5 -6×10 5 g / mol.

3. The highly elastic thermal transfer film substrate according to claim 2, characterized in that, The elastic reinforcing layer is prepared by supercritical carbon dioxide autoclaving process, with a saturation pressure of 14-20 MPa, a saturation temperature of 70-95℃, a saturation time of 2-4 hours, and a depressurization rate of 10-18 MPa / s. The resulting closed-cell foam film has an average cell diameter of 20-50 μm.

4. The highly elastic thermal transfer film substrate according to claim 3, characterized in that, In the barrier shaping layer, the degree of alcoholysis of polyvinyl alcohol is 88%-99%, the degree of polymerization is 1700-2400, and the nanocellulose whiskers are rod-shaped whiskers obtained by sulfuric acid hydrolysis of cotton pulp, with an aspect ratio of 15-30.

5. The highly elastic thermal transfer film substrate according to claim 4, characterized in that, In the surface substrate layer, the L-lactic acid content of polylactic acid is 96%-99%, and the number average molecular weight is 1×10⁻⁶. 5 -2×10 5 The grafting reaction was carried out using dicumyl peroxide as an initiator, with the amount of dicumyl peroxide being 0.15%-0.5% of the mass of polylactic acid. The grafting reaction of the polylactic acid modified by glycidyl methacrylate is carried out by reactive extrusion process. The temperature of each zone of the twin-screw extruder is 140-155℃ in the feeding section, 165-180℃ in the plasticizing section, 180-195℃ in the metering section, and 170-185℃ in the die head. The screw speed is 60-100 rpm.

6. The highly elastic thermal transfer film substrate according to claim 5, characterized in that, The elastic buffer underlayer is prepared by dissolving thermoplastic polyurethane particles in N,N-dimethylformamide to prepare a 14% (w / w) solution, adding 60nm nano-hydroxyapatite (5% of the mass of the thermoplastic polyurethane), and dispersing at 2500rpm for 25min to obtain a uniform dispersion. After vacuum degassing, the dispersion is cast onto a glass substrate and dried at 60℃ for 3.5 hours. Then, it is annealed at 105℃ for 35min to obtain an elastic buffer underlayer film. The elastic buffer underlayer is then hot-pressed onto the lower surface of the elastic reinforcement layer at 110℃ and 0.3MPa to obtain an elastic reinforcement layer with an elastic buffer underlayer.

7. The highly elastic thermal transfer film substrate according to claim 6, characterized in that, In the anchoring bonding layer, the acrylate structural unit of the acrylate-vinyl acetate copolymer emulsion is a copolymer of butyl acrylate and methyl methacrylate, with a mass ratio of butyl acrylate to methyl methacrylate of 50:50-60:

40. The vinyl acetate content is 15%-25% of the solid content of the copolymer emulsion. The waterborne polyurethane crosslinking agent is a blocked isocyanate crosslinking agent with a deblocking temperature of 110-130℃.

8. The highly elastic thermal transfer film substrate according to claim 7, characterized in that, In the release transfer layer, the polyethylene wax emulsion has a polyethylene wax melting point of 105-120℃ and an average particle size of 2-6μm, the polydimethylsiloxane has a viscosity of 350-1000cSt, and the nano-talc powder has an aspect ratio of 10-25.

9. The preparation process of a highly elastic thermal transfer film substrate according to any one of claims 1 to 8, characterized in that, Includes the following steps: S1. Preparation of elastic reinforcing layer: Polylactic acid granules and poly(3-hydroxybutyrate-3-hydroxyvalerate) granules are premixed at a mass ratio of 50:50-75:25 and fed into a twin-screw extruder for melt blending and granulation. The extrusion temperature zones are set as follows: feeding section 155-170℃, plasticizing section 170-185℃, metering section 180-195℃, and die head 175-190℃. The screw speed is 120-180 rpm. The resulting blended granules are fed into a high-pressure autoclave and supercritical carbon dioxide is introduced for saturation permeation. The saturation pressure is 14-20 MPa, the saturation temperature is 70-95℃, and the saturation time is 2-4 hours. Then, the pressure is released and foamed at a rate of 10-18 MPa / s to obtain a closed-cell foam film. S2. Preparation of the barrier and shaping layer: Aqueous dispersion of nanocellulose whiskers and aqueous solution of polyvinyl alcohol are mixed at a mass ratio of nanocellulose whiskers to polyvinyl alcohol of 1:2.5-1:5.

5. Aqueous solution of boric acid is added, with the amount of boric acid being 1.8%-3.5% of the mass of polyvinyl alcohol. The mixture is stirred and reacted at 75-85℃ for 30-50 min to form a precursor sol. The precursor sol is cast onto the upper surface of the elastic reinforcing layer obtained in S1 and dried in a constant temperature drying oven at 35-45℃ for 5-7 hours to form a semi-interpenetrating network gel film. Subsequently, the film is heat-treated in a hot air drying tunnel at 125-135℃ for 15-25 min to complete the crosslinking of boric acid and form an interpenetrating network structure film, thus obtaining an integrated composite film of elastic reinforcing layer and barrier and shaping layer. S3. Preparation of surface printing layer: Polylactic acid granules, glycidyl methacrylate monomer and dicumyl peroxide initiator are premixed. The amount of dicumyl peroxide is 0.15%-0.5% of the mass of polylactic acid. The mixture is fed into a twin-screw extruder for reactive extrusion grafting. The temperatures of each zone of the extruder are 140-155℃ in the feeding section, 165-180℃ in the plasticizing section, 180-195℃ in the metering section and 170-185℃ in the die head. The screw speed is 60-100 rpm. The resulting grafted modified granules are fed into a single-screw casting machine for casting into a film. The casting temperature is 190-210℃. After the cast film is cooled to room temperature, it is subjected to corona treatment to a dyne value of 48-56 to obtain the surface printing layer film. S4. The surface printing layer film obtained in S3 is hot-pressed onto the barrier shaping layer of the integrated composite film obtained in S2. The hot-pressing temperature is 135-150℃, the pressure is 0.3-0.5MPa, and the linear speed is 2-3m / min to obtain the substrate bottom layer. S5. Preparation of the release functional layer: On the surface printing layer of the substrate obtained in S4, an anchoring bonding layer mixture is first rolled onto it. The anchoring bonding layer mixture is composed of acrylate-vinyl acetate copolymer emulsion, nano silica sol and waterborne polyurethane crosslinking agent in a mass ratio of 15-25:2-4:1-3, with a wet film thickness of 30-50 μm. It is dried in an oven at 70-80℃ for 6-10 min. Then, a release transfer layer mixture is rolled onto the anchoring bonding layer. The release transfer layer mixture is composed of polyethylene wax emulsion, polydimethylsiloxane and nano talc powder in a mass ratio of 10-20:3-7:1-3, with a wet film thickness of 20-30 μm. It is dried in an oven at 80-90℃ for 4-6 min to obtain a high-elasticity heat transfer film substrate.

10. The preparation process of a highly elastic thermal transfer film substrate according to claim 9, characterized in that, The anchoring bonding layer mixture in step S5 is ultrasonically dispersed at 300-500W for 10-20 minutes before roller coating, and the release transfer layer mixture is high-speed dispersed at 2500-3500rpm for 15-25 minutes before roller coating; after drying in step S5, the rolled film is left to stand in a curing chamber at 40-50℃ for 60-84 hours.